Utilization of color theories in interior design student's color selection process - De Joya, Joanner Marius T. author; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
The study focused on how color theories are being viewed as undervalued despite of its various applications in interior design. Color selection among interior design students is often based on aesthetic preference alone this limits their application of color theories, which tackle various uses of colors to solve multiple design problems. The study aimed to describe the color selection process of interior design students identify factors influencing their color selection process and analyze how color theories are being perceived and utilized in Interior Design coursework. Color selection is deemed significant in institutional design to yield efficient functional applications. The qualitative research design used both descriptive and case study methods to analyze the colors used in institutional design coursework to recognize the factors influencing the color selection and how color theories are being utilized. The study was conducted using a semi-structured interview among 26 BS interior design students from 3 different schools. This population was comprised of 20% of the total population of third and fourth year students from each school, corresponding to around seven to 11 students from each school. Instruments such as the interview questionnaire, checklist questionnaire, audio recorder, and camera to take photos of the coursework projects of students were used. The study found out that most of the students integrate color applications towards the end of the design process. Multiple factors which include personal aesthetic preference and time constraints among other minor factors were the main reasons why color theories are often overlooked in the color selection process. The study therefore concludes that there is disconnection between what is learned from theories and what is applied in practice. A survey of a bigger sampling population size of interior design students and finding out the perceptions of instructors and lecturers regarding this issue are recommended.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Color in interior design